The Study on The Mechanical Properties and Performance Concrete of Precast Segmental Box Girder in Klang Valley Light Railway Transit Line Three (KVLRT3) for Package GS10 - Nordin, Abdul Qusyairi; Mahyeddin, Mohd Eizzuddin; Ismail, Akmal Hakim (Progress in Engineering Application and Technology, 2022)
To generate a better outcome of the precast product, the raw material used for casting the product is important due to implement the safety, long-lasting and trustworthy precast product. This research is using five number of segments as reference to conduct the research which is to specify the concrete grade that used for precast segmental box girder at KVLRT3 package GS10, analyzing the compressive strength test that using the test laboratory result and monitoring the performance of the segmental box girder according to the defects appear on segments. These results suggest that the potential of the concrete with the high workability and the great curing method can avoid the major defects of the precast segment.